2022
DOI: 10.7759/cureus.21721
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities and Vaccination Status of COVID-19 All-Cause Mortality at a Tertiary Care Center of Western India

Abstract: Introduction: COVID-19 vaccines have been found to be efficacious for preventing severe disease, yet breakthrough infections and deaths have occurred in a small proportion of vaccinated individuals. This study aimed to describe the vaccination status and comorbidities of COVID-19 all-cause deaths.Methods: This descriptive observational study was conducted at a tertiary care center in western India. A total of 310, RT-PCR positive COVID-19 deaths, aged 45 years and above irrespective of the cause of death (all-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Diabetes mellitus, hypertension, ischemic heart diseases, and chronic kidney diseases were the most common comorbidities reported by COVID-19 patients [ 85 , 86 ]. A recent study evaluating the possible reasons for the mortality following COVID-19 vaccination found that the deaths are due to pre-existing comorbidities and not due to the vaccination or the failure of vaccines to extend the protection [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus, hypertension, ischemic heart diseases, and chronic kidney diseases were the most common comorbidities reported by COVID-19 patients [ 85 , 86 ]. A recent study evaluating the possible reasons for the mortality following COVID-19 vaccination found that the deaths are due to pre-existing comorbidities and not due to the vaccination or the failure of vaccines to extend the protection [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in general, the reduced efficacy of the COVID-19 vaccine in the general population has now been established, due to the combination of various factors including the increase in variants, the reduction of the vaccination campaign, and the loss of efficacy of the vaccine over time [ 36 , 37 , 38 ]. Moreover, the presence of comorbidities in elderly subjects could influence vaccine efficacy [ 39 , 40 ]. The increase in SARS-CoV-2 variants is also referred to as "immune evasion" and could increasingly lead to a decrease in the effectiveness of anti-viral strategies, as well as that of the vaccine [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have published data about the cause of death in fatal cases of breakthrough SARS-CoV-2 infection [ 2 , 3 , 15 ]. A study from 2021 included patients fully vaccinated with Pfizer/BioNTech and the mortality rate was 22%, death occurring in individuals with a high rate of co-morbidities predisposing to severe COVID-19 disease, including hypertension (71%), diabetes (48%), congestive heart failure (27%), chronic kidney and lung diseases (24% each) [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, diabetes was the most common comorbidity found in 17.1% of the deaths, followed by hypertension in the study of Verma et al [3] assessing comorbidities and vaccination status of COVID-19-related deaths at a Tertiary Care Center of Western India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation